Local Quasitriangular Hopf Algebras - Zhang, S.; Gould, M.D.; Zhang, Yao-Zhong (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We find a new class of Hopf algebras, local quasitriangular Hopf algebras, which generalize quasitriangular Hopf algebras. Using these Hopf algebras, we obtain solutions of the Yang-Baxter equation in a systematic way. The category of modules with finite cycles over a local quasitriangular Hopf algebra is a braided tensor category.